Polyaniline Hybrids with Biological Tissue, and Biological Polymers as Physiological—Electroactive Materials - Mai Ichikawa; Masashi Otaki; Hiromasa Goto (Micro, 2023)
A sprout/polyaniline was synthesized via the chemical oxidative polymerization of aniline in the presence of natural sprout, based on a concept of cyborg plant composite. The composite consisted of both polyaniline and plants. The chemical structure was confirmed by infrared absorption spectroscopy measurements. Optical microscopy observation revealed that polyaniline was deposited into the micro-tissue of the sprout to form the conductive polymer bio-composite. Micro-optical fiber functions for the composite were visually confirmed. Furthermore, the sprout/polyaniline based organic diode exhibited an avalanche breakdown phenomenon. Next, a fucoidan/polyaniline composite as a physiological active material/conducting polymer composite was prepared. This composite showed good film-forming ability, electrochromism, and a micro-porous surface. This paper reports the preparation of conducting polymer composites with a combination of bio-tissue and bio-substance for the creation of bio-based electrically active organized architecture.